Failure of subarachnoid block in caesarean section in a tertiary hospital of Nepal - Deo, G P; Shrestha, S K; Shrestha, I N; Neupane, S; Ojha, H; Regmi, B S (Journal of Chitwan Medical College, 2017)
Although subarachnoid block is regarded as the most reliable, easy and safe anaesthetic technique during caesarean section, the possibility of failure has long been recognized. So, other methods of anaesthesia have to be employed at times. This study was performed in all patients of ASA I and II who underwent caesarean section at Chitwan Medical college, Bharatpur, Chitwan, Nepal from BS 1st Baisakh 2069 to 30th Chaitra 2072 (13 April 2012 to 12 April 2016) to find the rate of failure of subarachnoid block in Caesarean Section and need of additional anaesthetic supplementation. The total number of patients included in study was 6641 with mean age of 24.2 years and range of 16-39 years. Sub arachnoid block was performed with 25 G Quincke spinal needle at L3-L4 or L4-L5 spinal levels and solution injected was 2.20 ml of 0.5% hyperbaric Bupivacaine. Of the total 6641 patients who received subarachnoid block, 9.9% (n=661) required additional anesthetic supplements. Conversion to general anesthesia was needed in 252 (3.79%) patients. Rest 6.15% (n=409) could be operated with administration of additional intravenous anaesthetic agents.